Attitude of Teachers about the Use of Information and Communication Technology: Exploring Teachers' Attitudes towards ICT Use in Teaching (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The current review researches attitude of teachers teaching in Mahatma Gandhi Central University, Bihar towards the utilization of ICT both graphically and similarly. In this review endeavor has been taken to think about the attitude of teachers based on their sex and stream. For this review expressive cum causal near strategy was taken on, where 60 teachers were thought about arbitrarily. To gather information a normalized attitude scale was utilized. The discoveries of the review uncovered that close around 60 teachers communicated solid uplifting outlook and rest 40 inspirational perspective towards the utilization of ICTs in teaching-learning process. The discoveries of the concentrate additionally uncovered no critical distinction among the attitude of teachers concerning their sex and stream.